2020
DOI: 10.1002/iub.2370
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA PWRN1 is lowly expressed in osteosarcoma and modulates cancer proliferation and migration by targeting hsa‐miR‐214‐5p

Abstract: Background: We examined the expression pattern, clinical relevance, and molecular mechanisms of lncRNA PWRN1 in human osteosarcoma. Methods: qPCR was used to measure PWRN1 expressions in cell lines and tumor samples osteosarcoma. The correlations between PWRN1 and cancer patients' clinicopathological properties and survival were examined. PWRN1 was ectopically overexpressed in MG-63 and 143B cells to assess its function on cancer cell proliferation, cisplatin chemoresistance, and in vivo xenotransplant growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For example, FGD5-AS1 is an hub lncRNA in the TOF heart ceRNA network and can regulate SMAD4 by binding with hsa-miR-421 ( Zhang et al, 2021 ). It is worth mentioning that the four verified lncRNAs as a miRNA sponge are widely reported in cancers, such as the GATA3-AS1/miR-495-3p/CENPU axis in breast cancer ( Lin et al, 2021 ), and the PWRN1/miR-214-5p axis in osteosarcoma ( Shi et al, 2020 ). Based on the above analysis, we speculated that lncRNAs with ceRNA activity may be regulate the cell cycle, cell proliferation, and apoptosis by regulating heart-related mRNA and lead to the development of the CHD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FGD5-AS1 is an hub lncRNA in the TOF heart ceRNA network and can regulate SMAD4 by binding with hsa-miR-421 ( Zhang et al, 2021 ). It is worth mentioning that the four verified lncRNAs as a miRNA sponge are widely reported in cancers, such as the GATA3-AS1/miR-495-3p/CENPU axis in breast cancer ( Lin et al, 2021 ), and the PWRN1/miR-214-5p axis in osteosarcoma ( Shi et al, 2020 ). Based on the above analysis, we speculated that lncRNAs with ceRNA activity may be regulate the cell cycle, cell proliferation, and apoptosis by regulating heart-related mRNA and lead to the development of the CHD.…”
Section: Discussionmentioning
confidence: 99%
“…A distinctly downregulated lncRNA, Prader-Willi Region Non-Protein Coding RNA (PWRN1), was discovered during a study carried out by Shi et al and was found to be significantly correlated with advanced-stage metastasis, low survival rates in cancer patients, and chemoresistance. One of the major findings in this study was that cancer patients with low PWRN1 expression had much worse OS than those with high PWRN1 [ 62 ]. Additionally, when PWRN1 lncRNA was overexpressed in OS cell lines, the amount of cancer cell proliferation was drastically suppressed, and chemoresistance to cisplatin was markedly reduced.…”
Section: Non-coding Rnamentioning
confidence: 99%
“…Overexpression was also shown to suppress the in vivo growth of OS xenotransplants. Notably, miR-214-5p (a human microRNA) was identified as a possible ceRNA candidate for PWRN1, and the overexpression of miR-214-5p reversed the anti-cancer effects of PWRN1 on OS cell proliferation and chemoresistance [ 62 ].…”
Section: Non-coding Rnamentioning
confidence: 99%
“…Zhu et al demonstrated that the overexpression of miR‐142/miR‐22 reversed doxorubicin chemoresistance of osteosarcoma by inhibiting autophagy 6 . Shi et al revealed the miR‐214‐5p conferred cisplatin resistance in osteosarcoma 7 . miR‐519d‐3p (miR‐519d) is universally expressed in various cancer.…”
Section: Introductionmentioning
confidence: 99%